Mediating Role of Perceived Organizational Support in Relationship Between Teacher Self-Efficacy and Teacher Effectiveness - Al Munnir Abubakar; Tengku Faekah bt Tengku Ariffin; Fauziah Md Jaafar; Dinar Roudhotul Lailia (Madrosatuna: Journal of Islamic Elementary School, 2019)
The main aim of the study is to examines the relationship between teacher effectiveness and perceived organizational support in mediating by self-efficacy. Teacher effectiveness is the ability to produce gains on student achievement scores, taking account of a baseline measure of students’ performance. Perceived Organizational Support (POS) refers to employees' perception concerning the extent to which the organization values their contribution and is concerned about their wellbeing. Teacher self-efficacy is meant by teachers’ belief in their own ability to organize and execute courses of action essential to successfully achieving the specific teaching tasks in specific situations. The study is conceptual in nature and the research considers the drivers which motivate the teachers. The population of the study comprised secondary school teachers in Bauchi metropolitan. The proposed method of the study is quantitative which will be use questionnaire. The sample will be composed of males and females’ teachers. The study will adopt the descriptive survey design and all the information will collected through a questionnaire which largely had close-ended questions and one open-ended question.